2‐Amino‐5‐substituted‐1, 3, 4‐oxadiazole as chemosensor for Ni(II) ion detection: antifungal, antioxidant, DNA binding, and molecular docking studies. (30th January 2022) - Sultana, Razia; Arif, Rizwan; Rana, Manish; Ahmedi, Saiema; Mehandi, Rabiya; Akrema,; Manzoor, Nikhat; Rahisuddin,
Abstract: An oxadiazole derivative 2 was prepared by condensation reaction through cyclization of semicarbazone in the presence of bromine; the structural confirmation was supported by 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy, Fourier transform‐infrared spectroscopy, and liquid chromatography‐mass spectrometry. Its sensing ability towards Ni 2+ ion was examined showing a binding constant of 1.04 × 10 5 compared with other suitable metal cations (Ca 2+, Co 2+, Cr 3+, Ag +, Pb 2+, Fe 3+, Mg 2+, and K + ) using ultraviolet–visible (UV–vis) and fluorescence spectroscopic studies. The minimum concentration of Ni 2+ ions and limit of detection was found to be 9.4 μM. A job's plot gave the binding stoichiometry ratio of oxadiazole derivative 2 vs Ni 2+ ions as 2:1. Furthermore, the intercalative binding mode of oxadiazole derivative 2 with calf thymus DNA was supported by ultraviolet–visible (UV–vis) and fluorescent light, viscosity, cyclic voltammetry, time‐resolved fluorescence, and circular dichroism measurements. The molecular docking result gave the binding score for oxadiazole derivative 2 as −6.5 kcal/mol, which further confirmed the intercalative interaction. In addition, the antifungal activity of oxadiazole derivative 2 was also screened against several fungal strains ( C. albicans, C. glabrata, and C. tropicalis ) by broth dilution and disc diffusion methods. In antioxidant studies, the oxadiazole derivative 2 showed potential scavenging activity against 2, 2‐diphenyl‐1‐picrylhydrazyl and H2 O2 free radicals. Abstract : Sensing behaviour and biological application of synthesized oxadiazole derivative 2.